Incidence of Hepatitis-B Among Healthcare Professionals due to Medical Waste Handling (Journal of Dhaka Medical College, 2010)
The incidence of hepatitis-B among health care workers due to medical waste handling has been a subject of interest. A hospital base survey was done in Chittagong Medical College Hospital (CMCH), Chittagong during the period of April 2009 through June 2009 among health care workers was done to identify the problem. All types of health care workers especially those are very much vulnerable to needle stick puncture like nurses, ward boys, cleaners, laboratory technicians and doctors were included in this study.Total number of respondents was one hundred (sixty eight male and thirty two female). Age of the respondents ranged from 20-60 years with on average age of 24 ± 5.5 years. 62% of health care workers do not aware of hazards of medical waste. Only 38% are aware of infectious medical waste. Among them only 12% learned about the hazards of medical waste from hospital authority. Rest of them is aware of this implication from personal information. All of the health care workers claimed that they have no training on medical waste handling safely. Even they do not take any protective measure. 66% of the health care workers of different service type were punctured at least once or several times. So the puncture rate was counted with special attention. Sixty percent of ward boys, 90% of nurses, 25% of doctors and 80% of laboratory technicians were punctured once or several times within their job duration.These 5% health care workers were HbsAg positive. Among them one ward boy, two nurses, one cleaner and one laboratory technician were infected with hepatitis B virus. All of them had history of needle stick puncture. One HbsAg positive case was excluded from this study because of history of blood transfusion. Waste sharps are considered highly infectious medical waste causing hepatitis B frequently. Key words: Medical waste; occupational risk; hepatitis B. DOI: 10.3329/jdmc.v18i2.6275 J Dhaka Med Coll. 2009; 18(2) : 140-143